The Determinants of Capital structure in Ethiopian Private Commercial Banks: A Panel Data Approach - Abdu Mohammed Assfaw (Journal of Economics, Business, and Accountancy Ventura, 2020)
A wrong capital structure decision causes business frailer. However, still, what determinants optimal capital structure decision of companies remain the puzzles of many research scholars. This study is, therefore, aimed to investigate the determinants of the capital structure decision of private commercial banks in Ethiopia. The secondary data were obtained from audited annual financial reports of ten private commercial banks and the National Bank of Ethiopia covering the period of 2010-2018. The panel data were analyzed with a clustered robust random effect regression model. The study reveals that there is a significant positive relationship between earning volatility, size of banks, and taxation with leverage while profitability and asset tangibility are found to have a significant negative effect on the banks' leverage decision. The empirical findings of the study imply that the two capital structure theories, static trade-off and pecking order, are essentially explaining the capital structure decision of Ethiopian private commercial banks. Private commercial banks in Ethiopia should pay due attention to the microeconomic variables without overlooking the macroeconomic condition while articulating their optimal capital mix which can minimize the weighted average cost of capital and enhance the value of the company.